Root Surface Temperature Increases during Root Canal Filling In Vitro with Nd:YAG Laser-Softened Gutta-Percha. (8th June 2020) - Podolak, Błażej; Nowicka, Alicja; Woźniak, Krzysztof; Szyszka-Sommerfeld, Liliana; Dura, Włodzimierz; Borawski, Mariusz; Dembowska, Elżbieta; Lipski, Mariusz
Abstract : The aim of this in vitro study was to measure the temperature increases produced on the mesial and vestibular root surfaces of premolar teeth during a laser-softened gutta-percha obturation technique. We studied 12 extracted human premolar teeth with a single canal. After root canal cleaning and shaping, the teeth were obturated with gutta-percha that had been softened with a neodymium-doped yttrium aluminium garnet (Nd:YAG) laser (CTL 1503) at a wavelength of 1.064 nm. The laser setup parameters included a 30 Hz frequency and a 200 mJ/pulse with optical fiber tips of 0.320 mm diameter. A sectional warm gutta-percha condensation was used. Temperature changes on the whole mesial and vestibular outer surfaces of the roots were measured at approximately 2 s intervals with an infrared thermal imaging camera. A significantly higher increase in temperature was observed for the mesial root surface (7.5°C) compared to the vestibular surface (3.7°C) (p ≈ 0 ). The findings suggested that root canal filling with Nd:YAG laser-softened gutta-percha in premolar teeth is not likely to damage the surrounding periradicular tissues. To obtain valid temperature results, the measurement should be performed on the surface with the thinnest root wall.